Indigenous Students' Perceptions of Factors Contributing to Successful Law Studies - Carolyn Penfold (Legal Education Review)
While the under-representation of Aborigines and Torres Strait Islanders in formal education is apparent in pre-school and in the compulsory years of schooling, it becomes more marked at the higher levels of education, and by university level the under-representation is extreme. Studies have frequently looked at the needs of Aboriginal and Torres Strait Islander students and identified difficulties which these students face in the formal academic system. Lack of financial support, schooling background, pressure from family and community, health problems, inappropriate curricula, identity crises and negative stereotyping have all been identified as contributing to the poor rates of Indigenous participation and success in formal education. As a result, Indigenous Australians are under-represented in all professions, including law. Access to studies has become less a barrier since the introduction of discretionary admissions schemes to most Australian universities, but what Indigenous students experience while studying law clearly militates against them completing degrees. While the number of Indigenous law graduates has greatly increased in recent years,6 attrition is still of concern. Law schools continue therefore to search for ways to attract, retain and graduate Indigenous students. This study is a step in that process.